Insulinoma: a case report of a successful resective surgery - Machicado Rivero, Luis Enrique (2023)
Insulinoma is a pancreatic neuroendocrine tumor that produces hyperinsulinism and causes a severe lowering of blood glucose levels with chronic symptoms such as fainting. It is more common in males and can occur at any age, either as solitary or multiple neoplasms, the latter known to be part of the multiple endocrine neoplasia, type 1 (MEN 1) group. Insulinomas are rare and require resective surgery, with symptoms resolution being the marker of recovery. This article describes a case of insulinoma in a 51-year-old woman with a clinically typical presentation and signs and symptoms of hyperinsulinism. Laboratory tests revealed increased insulin secretion, while magnetic resonance imaging showed features of insulinoma, where the pancreatic tumor could be seen. This case was treated by surgical resection of the pancreatic tumor during an exploratory laparotomy, using the enucleation technique, which is described in detail herein. There were no intraoperative or postoperative complications, i.e., the result was successful in terms of health recovery. This surgical technique is used at Hospital Nacional Arzobispo Loayza in Lima, Peru, when facing cases such as the one described. This type of neoplasm is very uncommon, so it should be considered highly suspicious and, in this case, the images were essential for choosing the surgical resection. Other cases of insulinoma have been treated surgically at the Hospital; moreover at least one case of nesidioblastosis could not receive an adequate treatment.